Ruin of the Seaport: Causes of the Abandonment of Puerto Colombia and the Loss of a Coastal Gem - Romero, Pedro; Betts Alvear, Mark Michael (International Planning History Society Proceedings, 2024)
This article delves into the primary factors leading to the closure of Puerto Colombia's Seaport, shifting international port activity to the city of Barranquilla. As the construction of the western breakwater progressed to stabilize the mouth of the Magdalena River, the closure of the pier became a logical consequence, facilitating direct access for deep-draft vessels to Barranquilla's river port. The reasons behind the pier closure seem to be political, social, and economic. The national government, aiming to establish a secure route between the Caribbean Sea and the country's interior, leveraged direct access to the Magdalena River, prompting the relocation of commerce to Barranquilla. Additionally, concerns about the rising incidents of cargo theft during railway transportation and the significant investment in the construction of the western breakwater of the Magdalena River also played a role in the decision. This inquiry sheds light on the discourse emphasizing the advantages of relocating operations to Barranquilla, inadvertently overlooking the history and consequences of such a decision on the urban and social development of Puerto Colombia. To conduct this study, primary sources and relevant texts were employed, enabling an insightful historiographical analysis of documents and narratives. This approach successfully reconstructed the perspective on the issues in Puerto Colombia and Barranquilla. The findings obtained provide a solid foundation for future research related to the impact of infrastructure on urban and social configuration, the manipulation of historical discourse, and the study of coastal populations in their relationship with the environment.